Comparative Metabolic Properties of Aloe Vera Extracts and Sitagliptin in Diabetic Rats - Sobia Javaid, Maleeha Zafar, (Journal of Rawalpindi Medical College, 2022)
Introduction: Diabetes Mellitus, a global epidemic affecting millions of people is pretty challenging to cure as all the available antidiabetics have various health hazards, especially, in long-term administration. So, a safe alternative is always desired. Objective: To compare the metabolic (hypoglycemic and hypolipidemic) effects of Aloe Vera extracts with novel anti-diabetic medicine, “Sitagliptin” on diabetic rats. Materials and Methods: The study design was a Randomized Control Trial. The study was conducted in the Pharmacology department of Islamic International Medical College, Rawalpindi in collaboration with NIH, Islamabad, Pakistan, from September 2019 to August 2020. Adult, fifty Albino rats were taken and randomly grouped into A and B. After induction of type 2 diabetes with low dose streptozotocin, group B was subdivided; GroupB1 (Diabetic Control), Group B2 (Aloe Vera whole leaf treated), GROUP B3 (Aloe Vera gel treated), and Group B4 (Sitagliptin treated). Fasting blood sugar (FBS), Hemoglobin A1c (HbA1c), and triglycerides were measured. Statistical Analysis was done by SPSS version 25. A one-way ANOVA test was used for assessing any difference in the mean values. Post-hoc Turkey analysis was conducted to compare any inter-group mean differences. A p-value of <0.05 was considered significant. Results: On completion of study, Fasting blood sugar in Group A was 82.40mg/dl, Group B1 498.40 mg/dl, Group B2 89.30 mg/dl, Group B3 95.70 mg/dl, Group B4 93.00mg/dl; HbA1c in Group A was 3.71%, Group B1 11.84%, Group B2 4.02%, Group B3 4.17%, Group B4 3.73%; Serum triglycerides in Group A 125.40mg/dl, Group B1 221.00 mg/dl, Group B2 112.50 mg/dl, Group B3 129.70 mg/dl, Group B4 125.00 mg/dl respectively, showing significant improvement in Diabetes Mellitus in study subjects. Keywords: Aloe Vera gel, Sitagliptin, diabetes, glycated haemoglobin.